The Role of Humanitarian Logistics, Supply Chain Traceability, On Quality Healthcare: A Systematic Literature Review and Future Research Agenda - Akubia, Gilbert Korku; Gaffar, Vanessa; Andriana, Denny; Sultan, Mokh Adib (Business Education Program of Universitas Pendidikan Indonesia, 2024)
This systematic literature review examines the role of humanitarian logistics and supply chain traceability in delivering quality healthcare, especially in disaster management. The literature search was completed on October 31st, 2023, using the PRISMA method. After combining results, 864 papers were selected, followed by 118 screening based on title and abstract to ensure alignment with review objectives and performance measurement scope. It highlights the importance of timely and efficient responses during crises, focusing on the integration of supply chain traceability systems, technological advancements, and stakeholder collaboration. The review identifies challenges and opportunities, offers insights into best practices, and addresses ethical considerations. The findings aim to inform policymakers and organizations, providing a comprehensive understanding of how the intersection of humanitarian logistics and supply chain traceability enhances healthcare services' resilience and effectiveness in disaster-prone regions. In response to global challenges, this systematic literature review investigates the relationship between humanitarian logistics, supply chain traceability, and quality healthcare. It highlights the significance of supply chain traceability in improving transparency, accountability, and service quality. The review also looks at technological enablers like blockchain, RFID, and IoT, emphasizing stakeholder collaboration for optimal disaster response.